Loss of patient-reported outcome benefit over 8-year follow-up for operatively treated adult symptomatic lumbar scoliosis patients who required revision surgery for mechanical complications - Justin S. Smith; Michael P. Kelly; Elizabeth L. Yanik; Christine R. Baldus; Vy Pham; Hong Joo Moon; Jon D. Lurie; Charles Edwards; Steven D. Glassman; Lawrence G. Lenke; Stefan Parent; Jacob M. Buchowski; et al. (Journal of Neurosurgery: Spine, 2026)
OBJECTIVE Rates of revision surgery following operative treatment for adult symptomatic lumbar scoliosis (ASLS) are high, mostly due to mechanical complications, including proximal junctional failure (PJF) and pseudarthrosis/rod fracture (RF). How these revisions impact long-term clinical outcomes remains unclear. The aim of this study was to assess revision rates for the two most common mechanical complications (PJF and RF) and the potential impact of these revisions on patient-reported outcome measures over 8 years of follow-up for operatively treated patients with ASLS. METHODS This retrospective review used data from a multicenter prospective ASLS study to assess operative versus nonoperative ASLS treatment. Patients were 40–80 years of age with ASLS (Cobb ≥ 30° and Oswestry Disability Index [ODI] score ≥ 20 or revised Scoliosis Research Society 22-item questionnaire [SRS-22r] score ≤ 4.0 in pain, function/activity, and/or self-image domains). Patients who underwent long-segment posterior fusion (thoracic spine to sacrum) were assessed for the impact of revision due to mechanical complications on outcomes (SRS-22r subscore and ODI score). RESULTS Overall, 160 patients (141 female, median age 61.31 years) met inclusion criteria. Of these, 53 (33.1%) required revision (71 revisions, 25 for PJF and 46 for RF) for mechanical complications, with 1, 2, and 3 revisions in 39, 10, and 4 patients, respectively. By 8 years of follow-up, patients had a 38% estimated risk of revision for mechanical complications. The mean time to the first and second revisions was 3.0 years (SD 2.1) and 4.8 years (SD 2.3), respectively. In unadjusted analyses, patients with ≥ 1 revision had a significant negative impact on their 8-year ODI score (mean difference 9.40, 95% CI 3.68–15.13; p = 0.0013) and SRS-22r subscore (mean difference −0.27, 95% CI −0.49 to −0.05; p = 0.0141). Patients with ≥ 2 revisions experienced the greatest impact on both their ODI score (mean difference 14.48, 95% CI 4.89–24.07; p = 0.0031) and SRS-22r subscore (mean difference −0.38, 95% CI −0.74 to −0.02; p = 0.0361), with the impact exceeding the minimum detectable measurement difference for the ODI score (7) but not the SRS-22r subscore (0.4). In adjusted analyses, these differences were attenuated for patients with ≥ 2 revisions: ODI score (mean difference 14.14, 95% CI 4.52–23.75; p = 0.0040) and SRS-22r subscore (mean difference −0.30, 95% CI −0.67 to 0.06; p = 0.1001). CONCLUSIONS By the 8-year follow-up, revision surgery for mechanical complications was required in an estimated 38% of operative ASLS patients. Patients who underwent ≥ 1 revision had a significant negative impact on ODI score and SRS-22r subscore, and this impact was greatest with ≥ 2 revisions. These findings emphasize the need for better techniques to reduce mechanical complications in ASLS surgery.